Biochemical characterization of highly stable endolysins with a powerful and broad anti-Gram-negative lytic activity in the presence of weak acids - Oliveira, Hugo Alexandre Mendes (2014)
EMBO Conference on Viruses of Microbes III: Structure and Function - from Molecules to Communities (Programme and Abstract Book)